MEMANTINE, AS A P-GLYCOPROTEIN EXPRESSION MODULATOR, ENHANCES LEVETIRACETAM THERAPEUTIC RESPONSE IN EPILEPTIC PATIENTS - HARBY, SAHAR AHMED; NASSRA, RASHA A; F MEKKY, JAIDAA; M ALI, SAMIA; A ISMAIL, CHERINE (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The principal aim of the present study was to assess the importance of multidrug transporter; P-glycoprotein (P-gp) as a potential therapeutic target in patients with epilepsy. Can P-gp transporter expression modulation by memantine add to the standard antiepileptic drugs (AEDs) response? Methods: A cohort of 56 epilepsy patients was included in a 4 monthly visits prospective study. Patients were on levetiracetam (LEV) 1000 mg/ day alone or combined with other AEDs. They were randomly assigned into two groups; LEV only group including LEV-treated patients and LEV + memantine group including patients on LEV with add-on oral memantine 10 mg/day until the end of the study. During monthly follow-up visits, therapeutic responses were evaluated for each patient by recording the monthly seizures frequency. Blood samples were drawn from every patient twice (on the first and last visits) for assessment of P-gp mRNA expression level. Results: Fifty patients completed the study. At the end of 4th month, LEV only group showed a non-significant decrease in P-gp expression and seizure frequency compared to the 1st month, whereas, in LEV + memantine group, P-gp expression was significantly reduced and associated with significant seizure control. Conclusion: Memantine by hindering P-gp overexpression was apt to enhance LEV efficacy and exhibit a better seizure control.